The theatre of gaming: An investigation of the theatrical quality of games. - Reid, Kieran (My University, 2014)
While theatricality is a medium with a long and extensive history the study of digital games is relatively new, yet there are many parallels between the two that are both inherent and fundamental. This research aims to produce a theoretical synthesis between the two media by providing an analysis of the ontology and process of meaning making in both media. The role of the player in a digital game is a complex and ambiguous one where they perform a dual function as both audience and performer. The creation of narrative and meaning for the game’s player and the theatrical audience is often similar, relying on the creation of fully established and functioning fictional worlds to engage with. Primarily this is done through design and mise-en-scene strategies. Drawing from existing texts as examples, this research aims to explore the extent to which games adopt and have evolved from theatrical conventions of storytelling and aesthetics.
Keywords: Digital art--South Africa.